WETON CALCULATION AND LOCAL WISDOM IN JAVANESE TRADITIONAL WEDDINGS IN KARANG TANJUNG, LAMPUNG - Karsiwan; Lusi Handayani; Lisa Retno Sari (Jurnal Sosiologi Dialektika Sosial, 2026)
This study analyzes local wisdom in weton calculation in Javanese traditional wedding traditions in the Karang Tanjung Village community, Padang Ratu District, Lampung. The purpose of this study is to determine the meaning of local wisdom of weton calculation in Javanese traditional wedding traditions, the factors that still use weton calculation in society, and to analyze the form and meaning of weton calculation in Javanese traditional wedding traditions in Karang Tanjung Village. This study uses qualitative methods, data collected through in-depth interviews, and literature studies, analyzed with the theory of social action. The results of the study show that first, weton calculation is not just a method of divination, but also reflects local values ​​such as mutual cooperation, simplicity, kinship, and mutual respect, which are manifested in the preparation and implementation of Javanese traditional weddings in which the village community actively participates. Second, the factors that encourage the people of Karang Tanjung Village, Central Lampung, to continue using weton calculation in wedding traditions are local customs and culture, belief in the results of weton predictions, and personal experience. Third, weton calculations, which refer to the combination of days and markets in the Javanese calendar, play an important role in determining auspicious days for wedding events and rituals, involving the use of the Javanese calendar, monitoring the lunar cycle, and interpreting the symbolic meaning of each combination of days and markets.